Role of Prosecutors in Maximizing Fine Payments by Corruption Convicts at Boalemo Prosecutor's Office - Bahua, Salwa Salsabilah (Universitas Negeri Gorontalo, 2024)
The handling of corruption crimes aims not only to punish perpetrators but also to recover state losses through fines and restitution payments. In this context, prosecutors play a strategic role as executors of court decisions, ensuring the enforcement of fine payments by convicted corruption offenders. This study aims to analyze the role of prosecutors in maximizing fine payments by convicted corruption offenders at the Boalemo District Prosecutor's Office. The research employs a juridical-empirical method with a qualitative approach. Data were collected through interviews with prosecutors, document reviews, and direct observation of corruption cases handled by the Boalemo District Prosecutor's Office. The findings reveal that prosecutors play a crucial role in asset tracing, seizure, and auctioning to enforce fine payments. However, this role faces several challenges, such as limited resources, hidden assets by convicts, and weak inter-agency coordination. The study concludes that the effectiveness of prosecutors' roles can be enhanced through proactive approaches in asset tracing, the use of technology, and cross-agency cooperation at both national and international levels. With a more integrated strategy, the Boalemo District Prosecutor's Office can optimize state loss recovery and create a deterrent effect for corruption offenders.